The circulation of Johann Friedrich Herbart’s ideas in North American textbooks (1893–1920) - Valdemarin, Vera Teresa [UNESP] (My University, 2022)
This article adopts the historical perspective to understand the dynamics of the circulation of pedagogical ideas and identify movements of innovation, accommodation, and reinterpretation, usual in cultural processes. The analysis of the theme is limited to the educational ideas of Johan Friedrich Herbart (1776-1841) put into circulation in the United States of America, between the final decade of the 19th century and the initial decades of the 20th century. The documentary sources that support the analysis of this theme are two textbooks produced to guide the teaching practice of elementary school teachers, in training and practice: The elements of the general method based on the principles of Herbart (in the 1893 and 1907 editions) and Teaching by Projects, published in 1920, both by Charles A. McMurry (1857-1929), one of the leading North American disseminators of Herbartianism who, in addition to producing a vast bibliography, was a teacher, director and superintendent in primary schools, served in teacher training institutions and was one of the founders and Secretary of the National Herbart Society. The analysis of the diffusion cycle of Herbartian ideas, located between the Pestalozzian conceptions - the object lessons - and the conceptions of Progressive Education - the project method -, considered the interrelationship between agents, educational institutions, and pedagogical publications and followed since its renewing pretensions until its capitulation in the face of other trends and theories. Movements of innovation, adaptation, and reinterpretation of pedagogical concepts and practices were identified to give them relevance and meaning in different contexts of use
A circulação das ideias de Johann Friedrich Herbart em manuais didáticos norte-americanos (1893-1920)
Keywords: History of education; North-american herbartianism; Pedagogical ideas circulation; Textbooks